Entrance exam for candidates for master’s nursing studies — a 5-year retrospective analysis - Panczyk, Mariusz; Rebandel, Henryk; Belowska, Jarosława; Zarzeka, Aleksander; Gotlib, Joanna (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Aim of the study. Analyze admission criteria and assess the quality of the entrance exam for the MA program in Nursing at the Medical University of Warsaw (MUW) between 2009 and 2013. Material and methods. The study used the admission data of candidates for a Master’s degree program in Nursing in 2009–2013 (n = 2,257; median of age 23 years). The reliability level was established by estimating Cronbach’s alpha (reliability coefficient). ROC curve analysis for two categories (admitted/not admitted) was performed to estimate the selective capacity of the admission criteria. Results. An analysis of particular editions of the entrance exam demonstrated its insufficient reliability (a coefficient ranging between 0.429–0.559). The discriminatory power for the adopted admission criteria was diverse. The point score obtained in the exam has a significantly greater selection power than the criterion based on grade point average (ROC curves, P < 0.00001). A high discriminatory power of the test questions regarding “Clinical Nursing” was also observed. Conclusions. The role of GPA and scoring scientific activity needs to be reduced and, at the same time, the importance of the results of the exam needs to be increased. Moreover, improvements in the quality parameters of the exam test questions are needed, so as to achieve a better discriminative ability of this selective tool.